Survey of Equine Referring Veterinarians' Satisfaction with Their Most Recent Equine Referral Experience. (22nd February 2018) - Best, C.; Coe, J.B.; Hewson, J.; Meehan, M.; Kelton, D.
Abstract : Background: Little is known about the veterinary referral process and factors that contribute to positive outcomes. Objective: To investigate equine referring veterinarians' (rDVMs') satisfaction with their most recent referral experience and compare rDVM and specialist perspectives. Sample: 187 rDVMs and 92 specialists (referral care providers). Methods: Cross‐sectional observational study. An online survey was administered to both rDVMs and specialists. Referring veterinarian satisfaction with their most recent referral experience was evaluated. Both rDVMs and specialists were asked to identify factors influencing a rDVM's decision where to refer, and the top 3 factors they perceive are barriers to referral care. Results: Median rDVM satisfaction with their most recent referral care experience was 80 of 100 (mean, 75; range, 8–100). Referring veterinarians provided the lowest satisfaction score for the item asking about "The competition the referral hospital poses to your practice" (mean, 56.96; median, 62; range, 0–100). The top factor rDVMs identified as influencing their decision where to refer was "quality of care, " whereas specialists identified "quality of communication and updates from the clinician." Referring veterinarians' top barrier to referral care was "high cost of referral care, " and for specialists was "poor service provided to the client by the referral hospital." Conclusions and Clinical Importance: Referring veterinarians generally were satisfied with referral care, but areas exist where rDVMs and specialists differ in what they view as important to the referral process. Exploring opportunities to overcome these differences is likely to support high quality care.